STUDENTS’ PERCEPTION OF USING YOUTUBE IN VOCABULARY MASTERY - Ririn Nurjana Mokodompit; Nurmin F. Samola; Ignatius Javier C. Tuerah (JELLT (Journal of English Language and Literature Teaching), 2020)
The purpose of this study is find how students’ perceptions of using YouTube in Vocabulary Mastery. YouTube is online Video sharing platform which allows users to upload, view, and share video from all over the world therefore can also as media online learning especially in mastering vocabulary. The researchers use quantitative research and the sample of this research is 37 students in seven semester of English Education Department, Universitas Negeri Manado. Researchers use questionnaire as instrument in collecting the data. Questionnaire is one of research instrument, which aims for collecting data in survey research and also can be thought of as kind of written interview. The type of questionnaire that used in this research is closed-ended questionnaire. It is used like scale questionnaire in data collection and analyzed in statistical descriptive. Optional for the questioner measuring from strongly agrees, agree, neutral, disagree and strongly disagree. The result in this research is found by seeing the responses of students after distributing the questionnaire and collecting the data. As the result mostly students give positive perception using YouTube in vocabulary mastery and even give good impact to their ability especially in class environment.